Primary cutaneous chrysosporium infection following ear piercing: A case report - Poonkiat Suchonwanit (2018)
© 2015 S. Karger AG, Basel. Chrysosporium is a large genus of saprophytic fungi that is commonly found in the soil. Infection caused by this organism is rare in humans and typically occurs in immunocompromised patients. Primary cutaneous Chrysosporium infection is relatively rare and has been reported in a heart transplant patient. The prognosis is usually favorable, but very poor in the setting of persistent profound immunosuppression. We herein report a case of primary cutaneous Chrysosporium infection following ear piercing in an immunocompetent patient. It is important for clinicians to consider this condition in patients with slow-onset skin and soft tissue infection following cutaneous injury, even in an immunocompetent setting.